Thinking with theory in qualitative research : viewing data across multiple perspectives - Jackson, Alecia Youngblood , 1968-; Mazzei, Lisa A. (Routledge, 2012)
"This book uses a common data set and utilizes various theoretical perspectives through which to view data. "Plugging in" the theory and the data produces a variety of readings through the application of these theorists and their concepts: - Derrida - Deconstruction - Spivak - Postcolonial Marginality - Foucault - Power/Knowledge - Butler - Performativity - Deleuze - Desire - Barad - Material Intra-activity By presenting detailed examples of how qualitative researchers can think about data and analysis differently given these various frames and concepts, the authors demonstrate how to produce different knowledge from their work. It challenges qualitative researchers to use theory to accomplish a rigorous, analytic reading of qualitative data. Thinking With Theory In Qualitative Research pushes against traditional qualitative data analysis: mechanistic coding, reducing data to themes, and writing up transparent narratives that do little to critique the complexities of social life; such simplistic approaches preclude dense and multi-layered treatment of data. The authors show that "thinking with theory" pushes research and data and theory to its exhaustion in order to produce knowledge differently. By refusing a closed system for fixed meaning (i.e., transferable patterns and themes generated from coding data with reductive language), the authors engage a new analytics to keep meaning on the move. The result is an extension of thought beyond an easy sense. Special features of the book include schematic cues to help guide the reader through what might be new theoretical terrain, interludes that explain the possibilities of thinking with a particular concept and theorist, detailed chapters that plug the same data set into a specific concept, and lists of suggested readings"--Provided by publisher